F-Spondin Is the Signal by Which 2-Methoxyestradiol Induces Apoptosis in the Endometrial Cancer Cell Line Ishikawa - Orihuela-Diaz, P; Godoy-Guzman, C; Mena-Silva, J; Diaz-Saldivar, P; Guajardo-Correa, E (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
The metabolite 2-methoxyestradiol (2ME) is an endogenous estrogen metabolite with potential therapeutic properties in reproductive cancers. However, the molecular mechanisms by which 2ME exerts its anticancer activity are not well elucidated. The purpose of this study was to determine the molecular signals associated with the apoptotic effects of 2ME in a human endometrial cancer cell line. Ishikawa cells were treated with non-apoptotic (0.1 µM) or apoptotic concentrations (5 µM) of 2ME, and 12 hours later mRNA levels for Scd2, Snx6, and Spon1 were determined by real-time PCR. We then investigated by immunofluorescence and Western blot the expression and distribution of F-spondin, encoded by Spon1, in Ishikawa cells treated with 2ME 5 µM at 6, 12, or 24 h after treatment. The role of estrogen receptors (ER) in the effect of 2ME on the Spon1 level was also investigated. Finally, we examined whether 2ME 5 µM induces cell death in Ishikawa cells pre-incubated with a neutralizing F-spondin antibody. Non-apoptotic or apoptotic concentrations of 2ME decreased Scd2 and increased Snx6. However, Spon1 was only increased with the 2ME apoptotic concentration. F-spondin protein was also increased at 12 and 24 h after 2ME treatment, while 2ME-induced Spon1 increase was independent of ER. Neutralization of F-spondin blocked the effect of 2ME on the cell viability. These results show that F-spondin signaling is one of the components in the apoptotic effects of 2ME on Ishikawa cells and provide experimental evidence underlying the mechanism of action of this estrogen metabolite on cancer cells. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.